Inhibition, Disinhibition, and the Control of Action in Tourette Syndrome. Issue 11 (November 2015) - Jackson, Georgina M.; Draper, Amelia; Dyke, Katherine; Pépés, Sophia E.; Jackson, Stephen R.
Abstract : Tourette syndrome (TS) is a neurological disorder characterized by vocal and motor tics. TS is associated with impairments in behavioral inhibition, dysfunctional signaling of the inhibitory neurotransmitter GABA, and alterations in the balance of excitatory and inhibitory influences within brain networks implicated in motor learning and the selection of actions. We review evidence that increased control over motor outputs, including the suppression of tics, may develop during adolescence in TS and be accompanied by compensatory, neuromodulatory, alterations in brain structure and function. In particular, we argue that increased control over motor outputs in TS is brought about by local increases in 'tonic' inhibition that lead to a reduction in the 'gain' of motor excitability. Trends: Tourette syndrome (TS) has been linked to impairment of inhibitory function. Recent evidence provides support for reduced physiological inhibition as a factor in the occurrence of tics, but there is little evidence that TS is linked to impairment in behavioral inhibition. A widely held view is that control over tics is accomplished through increased functional and structural connectivity between frontal brain regions and motor cortex. Emerging evidence provides little support for this view, but indicates that, to the extent that structural and functional connectivity are increased in TS, such connectivity is disorganized and is associated with increases in tic severity. Control over motor outputs in TS, including tics, may be brought about by increases in GABA-mediated 'tonic' inhibition within higher-order motor regions that lead to a reduction in the 'gain' of motor excitability.